Difference and dissent in the neoliberal university: relational geographies of race, caste, and violence. Issue 3 (4th May 2021) - Thomas, Susan
ABSTRACT: Higher education in both India and the United States has been experiencing a neoliberal turn discernable since the 1990s. At the same time, tensions around who does and does not belong on campuses in the neoliberal moment have also plagued universities in the two nations. Drawing from critical geography, this article employs a 'relational comparison' approach to examine together two much-publicized instances of such tensions, one concerning Black students at Washington DC's American University and the other centered around Dalit students at Hyderabad's University of Hyderabad. I consider how the agendas, routines, and narratives inscribed in and by the institutional cultures of the two universities, both of which are being re-worked by neoliberal logics, cultivate the terrain for moments of race and caste violence. I argue that such moments work dialectically with the project of neoliberalizing the university, serving to reproduce race and caste difference and regulate student political life.